2018
DOI: 10.3390/polym10060604
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic Devices Based on Poly(2,6-di(9H-carbazol-9-yl)pyridine)-Type Polymer Films and PEDOT-PSS

Abstract: 2,6-Di(9H-carbazol-9-yl)pyridine (DiCP) was synthesized and its corresponding homopolymer (PDiCP) and copolymers (P(DiCP- co -CPDT), P(DiCP- co -CPDT2), P(DiCP- co -CPDTK), and P(DiCP- co -CPDTK2)) were synthesized electrochemically. The anodic copolymer with DiCP:cyclopentadithiophene ketone (CPDTK) = 1:1 feed molar ratio showed high transmittance change (Δ T %) and colouration efficiency ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 52 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…The η can be determined using the formula [ 29 ]: where Q d refers to the amount of injected/ejected charge per unit active area. The η values of PtCz, P(tCz- co -bTP), P(tCz- co -CPDT), P(tCz- co -DTC), and P(tCz- co -CPDTK) films are calculated to be 42.6 cm 2 C −1 at 760 nm, 67.6 cm 2 C −1 at 967 nm, 76.7 cm 2 C −1 at 864 nm, 78.3 cm 2 C −1 at 870 nm, and 62.5 cm 2 C −1 at 984 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The η can be determined using the formula [ 29 ]: where Q d refers to the amount of injected/ejected charge per unit active area. The η values of PtCz, P(tCz- co -bTP), P(tCz- co -CPDT), P(tCz- co -DTC), and P(tCz- co -CPDTK) films are calculated to be 42.6 cm 2 C −1 at 760 nm, 67.6 cm 2 C −1 at 967 nm, 76.7 cm 2 C −1 at 864 nm, 78.3 cm 2 C −1 at 870 nm, and 62.5 cm 2 C −1 at 984 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…627 nm than that of homopolymers (PDTCs). Table 4 lists ∆T's comparisons of P(DTC-co-TF)/PEDOT-PSS ECD with reported ECDs, showing that P(DTC-co-2BTP)/PEDOT-PSS ECD displays a higher ∆T than those reported for PETI/PEDOT [41], P(PS-Carb)/PEDOT [26], P(BCO)/PEDOT [42], and P(DiCP-co-CPDTK)/PEDOT-PSS ECDs [43]. The τ b and τ c of PDTC/PEDOT-PSS, P(DTC-co-BTP)/PEDOT-PSS, P(DTC-co-BTP2)/ PEDOT-PSS, P(DTC-co-TF)/PEDOT-PSS, and P(DTC-co-TF2)/PEDOT-PSS ECDs in Table 6 are in the range of 0.3-0.9 s. τ b and τ c of five ECDs were shorter than their corresponding anodes in 0.2 M LiClO 4 /ACN, revealing the ECDs switched color quicker than the anodes in 0.2 M LiClO 4 /ACN from the colored to the bleached state [44].…”
Section: Electrochromic Switching Of Anodic Polymersmentioning
confidence: 96%
“…627 nm than that of homopolymers (PDTCs). Table 4 lists ΔT's comparisons of P(DTC-co-TF)/PEDOT-PSS ECD with reported ECDs, showing that P(DTC-co-2BTP)/PE-DOT-PSS ECD displays a higher ΔT than those reported for PETI/PEDOT [41], P(PS-Carb)/PEDOT [26], P(BCO)/PEDOT [42], and P(DiCP-co-CPDTK)/PEDOT-PSS ECDs [43]. Figure 8 showed the potential stepping of PDTC/PEDOT-PSS, P(DTC-co-BTP)/PEDOT-PSS, P(DTC-co-BTP2)/PEDOT-PSS, P(DTC-co-TF)/PEDOT-PSS, and P(DTC-co-TF2)/PEDOT-PSS ECDs between colorless and colorful states with a residence time of 5 s. The ∆OD, ∆T, τ b , and τ c of PDTC/PEDOT-PSS, P(DTC-co-BTP)/PEDOT-PSS, P(DTC-co-BTP2)/PEDOT-PSS, P(DTC-co-TF)/PEDOT-PSS, and P(DTC-co-TF2)/PEDOT-PSS ECDs are displayed in Table 6.…”
Section: Electrochromic Switching Of Anodic Polymersmentioning
confidence: 97%
“…The list of electrochromic materials include inorganic systems (e.g., WO 3, V 2 O 5, NiO [7,8,9] and Prussian blue [10]) and organic ones (e.g., viologens, polyaniline, and poly(3,4-ethylenedioxythiophene)). Compared with inorganic electrochromic materials, organic electrochromic materials have advantages such as a broader color palette, higher coloration efficiency, and greater optical contrast [11,12,13,14,15,16]. In addition, recent studies have demonstrated the suitability of a large number of techniques, including spray coating, ink jet, and doctor blading, for deposition of thin films of conducting polymers with good control of the process [17,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%